From Local Heritage to Global Market: Reframing Digital Halal Branding through Storytelling in Batik Pesisir SMEs Pekalongan - Alya Falasifah; Aditya Agung Nugraha (Journal of Management, Finance, and Accounting Research, 2026)
In Indonesia, the halal creative industry has experienced significant growth; however, SMEs in this sector face unique challenges in adopting digital marketing, particularly for products rooted in cultural heritage with deep philosophical significance. This study aims to analyze the digital marketing strategies employed by Batik Pesisir Pekalongan SMEs in building their brands amidst the dominance of mass e-commerce. The phenomenon of rising Muslim consumer awareness regarding the halal status of creative products has not been matched by optimal digital branding efforts by the majority of halal SMEs. This study employs a qualitative approach using the case study method; data was collected through in-depth interviews with the owners and managers of Batik Pesisir Pekalongan, participatory observation of social media activities, and analysis of relevant documents. The research findings indicate that Batik Pesisir employs a selective, storytelling-based digital marketing strategy. Unlike other SMEs that rely on direct transactions via e-commerce, Batik Pesisir utilizes social media as a means to build brand awareness, convey the philosophy of batik, and foster an emotional connection with consumers. This study contributes to the development of digital marketing theory for heritage-based halal products and provides practical implications for halal creative SMEs in designing digital strategies tailored to the characteristics of their respective products. The research findings indicate that strengthening a halal brand does not solely depend on formal certification but is shaped through the consistent communication of Islamic values, trust, and transparency on social media. [Di Indonesia, industri kreatif halal telah mengalami pertumbuhan yang signifikan; namun, UMKM di sektor ini menghadapi tantangan unik dalam mengadopsi pemasaran digital, terutama untuk produk-produk yang berakar pada warisan budaya dengan makna filosofis yang mendalam. Penelitian ini bertujuan untuk menganalisis strategi pemasaran digital yang diterapkan oleh UMKM Batik Pesisir Pekalongan dalam membangun merek mereka di tengah dominasi e-commerce skala besar. Fenomena meningkatnya kesadaran konsumen Muslim mengenai status halal produk-produk kreatif belum diimbangi dengan upaya branding digital yang optimal oleh sebagian besar UMKM halal. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus; data dikumpulkan melalui wawancara mendalam dengan pemilik dan manajer Batik Pesisir Pekalongan, observasi partisipatif terhadap aktivitas media sosial, serta analisis dokumen-dokumen yang relevan. Hasil penelitian menunjukkan bahwa Batik Pesisir menerapkan strategi pemasaran digital yang selektif dan berbasis narasi. Berbeda dengan UMKM lain yang mengandalkan transaksi langsung melalui e-commerce, Batik Pesisir memanfaatkan media sosial sebagai sarana untuk membangun kesadaran merek, menyampaikan filosofi batik, dan menumbuhkan ikatan emosional dengan konsumen. Studi ini berkontribusi pada pengembangan teori pemasaran digital untuk produk halal berbasis warisan budaya dan memberikan implikasi praktis bagi UMKM kreatif halal dalam merancang strategi digital yang disesuaikan dengan karakteristik produk masing-masing. Temuan penelitian menunjukkan bahwa penguatan merek halal tidak hanya bergantung pada sertifikasi formal, tetapi juga dibentuk melalui komunikasi yang konsisten mengenai nilai-nilai Islam, kepercayaan, dan transparansi di media sosial.]